Theoretical study of multi-stage and multi-feeding variable pressure humidification-dehumidification (VP-HD) desalination systems - Zohreh Rahimi-Ahar; M. Hatamipour (Iranian Journal of Chemical Engineering)
Humidification-dehumidification (HD) desalination has been identified as a sustainable, reliable, and energy-efficient technology for producing freshwater on a small scale. VP-HD systems operated at one-stage, multi-stage, and multi-feeding vacuum humidification-over atmospheric pressure dehumidification arrangements can be the recent modifications of an HD system. The present study offers a theoretical investigation and experimental verification of two VP-HD systems, encompassing both sub-atmospheric pressure humidification and over-atmospheric dehumidification. Two designs are evaluated, one comprising a three-stage humidification setup and the other featuring a three-feeding one-stage humidification apparatus. The results show which design has better performance than previous conventional and variable pressure HD systems. The parametric analysis reveals that an upsurge in freshwater generation is observed with an increase in air temperature, feed salinity, and a decrease in humidifier pressure. Additionally, an optimal water-to-air ratio is identified. The study further highlights that multi-stage humidification yields better results concerning freshwater productivity and specific power consumption. Three-stage humidification is found to be the most efficient in terms of freshwater production and specific power consumption, achieving the highest values of 1.93 L h-1 m-2 and 0.21 kWh L-1, respectively. The agreement between theoretical and experimental outcomes is deemed satisfactory.